Classical pediatric Hodgkin lymphoma in very young patients: the Italian experience. Issue 3 (23rd February 2019) - Farruggia, Piero; Puccio, Giuseppe; Locatelli, Francesco; Vetro, Mariarita; Pillon, Marta; Trizzino, Angela; Sala, Alessandra; Buffardi, Salvatore; Garaventa, Alberto; Rossi, Francesca; Bianchi, Maurizio; Zecca, Marco; et al.
Abstract: Many studies have reported a more favorable outcome in younger patients with Hodgkin lymphoma (HL). The aims of this study were to find an appropriate age cutoff able to identify low-risk children and to describe the natural history of 135 very young patients affected by classic HL (cHL). The best age cutoff was identified at 7 years of age. EFS ( p = .0451) and PFS ( p = .00921) were significantly better in the group of younger patients. The OS rate at 10 years was 97.0% in the younger group and 92.5% in the older one ( p = .0448). However, age was not found to be an independent prognostic factor in multivariate analysis and the better prognosis in younger patients seems to be related to more favorable disease characteristics at presentation.